PERSEPSI GURU ATAS PENGEMBANGAN KARIR, BUDAYA ORGANISASI, PENDIDIKAN DAN PELATIHAN TERHADAP PRESTASI KERJA GURU SEKOLAH MENENGAH KEJURUAN FLORA BEKASI - Yosafat Puji Hastoko (Human Capital Development, 2018)
Purpose- The purpose of this study specifically is to reveal how much the contribution of career development factors, the organizational culture of education and training, to the work performance of Bekasi flora Vocational School teachers. The research method used is quantitative with descriptive correlational analysis. Design/methology/approach- The objects that were sampled in this study were 63 teaching teachers in the Bekasi Flora VOCATIONAL SCHOOL, sampling was done by a saturated sample method in which all populations were sampled. Data collection was conducted using a questionnaire instrument developed from variables (X1) career development (X2) organizational culture (X3) education and training (training) and variables (Y) teacher work performance. Data analysis using multiple linear regression techniques. Findings- Based on the results of the research separately, it can be seen the influence of career development factors (X1 on Y), 42.3%, organizational culture (X2 against Y), 68.7%, while education and training on teacher work performance (X3 against Y) 72.4%. Simultaneously the factors of career development, organizational culture, education and training (X1, X2 and X3 against Y) were 75.7%.